Prawo czy forma? Francisa Bacona koncepcja prawidłowości w przyrodzie - Luc, Joanna (Filozofia Nauki, 2019)
The aim of this paper is to analyze the terms “law” (of nature) and “form” in two works of Francis Bacon: the Novum Organum and The Advancement of Learning. The term “form” belongs to the scholastic tradition, whereas the term “law” is crucial for modern scientific methodology. The analysis starts with general characteristics of both terms and then traces them in Bacon’s writings. Both terms turn out to be important for Bacon, but it is argued that to fully understand his approach, his nominalistic tendencies should be acknowledged as well.